2014
DOI: 10.1016/j.jval.2014.03.1652
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Incidence And Characteristics Of Patients With Choroidal Neovascularization Secondary To Pathologic Myopia In A Representative Canadian Cohort

Abstract: A283or previous use of inhaled anticholinergics was not associated with a significant increased risk of AACG (active use: adjusted OR 1.32, 95% CI 0.83-2.10; non-active use: adjusted OR 1.13, 95% CI 0.72-1.75) compared to non-use, adjusting for use of other medications related to AACG. ConClusions: A relationship between the use of inhaled anticholinergics and the risk of AACG was not observed in this COPD population. However, the findings are limited due to the small sample size of the events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Specifically, fundus images were evaluated for the presence of the following: (1) MMD based on the international Meta Analyses of Pathologic Myopia (META-PM) classifications, where the presence of MMD was defined as META-PM MMD category 2 (diffuse atrophy) or worse (e.g., Figure 1A ), or the presence of plus signs (e.g., lacquer cracks, mCNV, or Fuchs spots; Figure 1B ) ( 6 ), (2) PPA (e.g., Figure 2A ), and (3) myopic tilted disc (e.g., Figure 2B ) defined as an optic disc with a ratio of minimal to maximal disc diameter of 0.75 or less and was assessed via the use of fundus photography ( 31 ). Given that Fuchs spot is considered a quiescent mCNV ( 32 ), and mCNV is one of the most commonly described features of PM ( 33 ), we included both active and quiescent forms in our prevalence of mCNV.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, fundus images were evaluated for the presence of the following: (1) MMD based on the international Meta Analyses of Pathologic Myopia (META-PM) classifications, where the presence of MMD was defined as META-PM MMD category 2 (diffuse atrophy) or worse (e.g., Figure 1A ), or the presence of plus signs (e.g., lacquer cracks, mCNV, or Fuchs spots; Figure 1B ) ( 6 ), (2) PPA (e.g., Figure 2A ), and (3) myopic tilted disc (e.g., Figure 2B ) defined as an optic disc with a ratio of minimal to maximal disc diameter of 0.75 or less and was assessed via the use of fundus photography ( 31 ). Given that Fuchs spot is considered a quiescent mCNV ( 32 ), and mCNV is one of the most commonly described features of PM ( 33 ), we included both active and quiescent forms in our prevalence of mCNV.…”
Section: Methodsmentioning
confidence: 99%
“…Willis et al [57] reported a prevalence of 0.017% for CNV in American people over 18y and 0.0079% in the over 65-year population. The majority of the studies presented the prevalence of CNV in patients with pathological myopia [58] ; for example, Wong et al [59] reported a prevalence of 5.2%-11.3% in different ethnic populations and Zaour et al [60] reported a prevalence of 6.2% in the Canadian population. The above values indicate that a higher percentage of the Iranian elderly population had CNV.…”
Section: Central Retinal Artery Occlusionmentioning
confidence: 99%